Pola Pemberdayaan UMKM Melalui Pendidikan Ekonomi Kewirausahaan Sebagai Upaya Memperkuat Ketahanan Ekonomi Rumah Tangga Keluarga di Kabupaten Pinrang - Darwis, Nirwana; Mustari; Hasan, Muhammad; Dinar, Muhammad; Judijanto, Loso (Journal of Economic Education and Entrepreneurship Studies, 2023)
This study aims to determine the pattern of MSME empowerment through entrepreneurial economic education as an effort to strengthen the economic resilience of family households in Pinrang Regency. This research uses data collection techniques in the form of observation, interview and documentation methods. MSME actors in Watang Sawitto District, Pinrang Regency which consists of several types of businesses including: culinary businesses, fashion businesses, cosmetic businesses, and grocery stores. Data analysis techniques in this study used data reduction, data presentation, and conclusion drawing. The results of this study indicate that entrepreneurial economic education plays a key role in improving the capacity of MSMEs in Pinrang district in facing economic challenges. In the perspective of informal entrepreneurial economic education, this approach emphasizes practical learning conducted in the field, providing opportunities for existing MSME actors in Pinrang district to hone their skills and knowledge. On the other hand, non-formal entrepreneurial economic education provides structure and more structured teaching, often through training. Both have their own added value in improving entrepreneurial skills. The realization of an empowerment pattern that combines these two perspectives can be an effective solution to strengthen the economic resilience of family households in Pinrang district.